Discovering servant leadership attributes for conflict management at Kumpulan Wang Simpanan Pekerja (KWSP) Seberang Jaya Pulau Pinang / Hasriyah Mohd Narudin and Nor Amyza Hamzah - Mohd Narudin, Hasriyah; Hamzah, Nor Amyza (2010)
This study proposes to identify the relationship between attributes of servant leadership towards conflict solving in Kumpulan Wang Simpanan Pekerja (KWSP) Seberang Jaya Pulau Pinang. This research will use three attributes of servant leadership which are vision, trust and empowerment. The sample size for this research is 108 employees at KWSP. The independent variables analyzed were vision, trust and empowerment while the dependent variable was conflict management. The data was gathered by distributed questionnaire and analyzed by using correlation coefficient analysis of Statistical Package for Social Science (SPSS) version 16.0.